P724 Delaying an infliximab infusion by more than 3 days is associated with a significant reduction in trough levels. (15th January 2020) - Ungar, B; Ben-Shatach, Z; Ziv-Baran, T; Fudim, E; Yavzori, M; Picard, O; Selinger, L; Weiss, B; Kopylov, U; Eliakim, R; Ben-Horin, S
Abstract: Background: An association between higher infliximab-trough-levels (TL) and better outcomes has been demonstrated among IBD patients. Although standard scheduled infliximab therapy regimen consists of infusions at pre-defined time-points (weeks 0, 2, 6 and every 8 weeks), short-period deviations from therapeutic schedule are common in 'real life', especially during maintenance period (due to weekends, holidays, concurrent illnesses, etc.). We aimed to determine whether short-period deviations from infusion-schedule affect infliximab-TL and therapy outcome. Methods: This was a retrospective study, analysing sera from all IBD patients receiving infliximab maintenance-therapy every 8 weeks in a tertiary medical centre. Associations between time since last infusion and TL were analysed. Clinical scores were recorded prospectively on infusion days and baseline demographic parameters were derived from patients' charts. Statistical analysis was performed using generalised estimating equations. Results: In total, 2088 sera of 302 maintenance-period infliximab-therapy-patients were included (median TL 4.1 μg/ml, IQR 2.3–6.5 μg/ml). A delay beyond 3 days in infusion ( n > 59 days since last infusion) was demonstrated as significantly affecting TL (mean difference in TL 1 μg/ml, 95% CI 0.03–1.9 μg/ml, p < 0.04). A sub-analysis was performed for 60 maintenance-period infliximab-therapy-patients with >10 consecutive TL measurements (1226 measurements in total), with adjustment for background parameters (gender, infliximab dose, disease type, concomitant immunomodulator, age and weight). A delay of >4 days from scheduled infusion resulted in a statistically significant decline in infliximab trough levels (mean difference in TL 1.45 μg/ml, 95% CI 0.61–2.2 μg/ml, p < 0.001). Finally, deviation from infusion schedule was analysed in association with clinical remission status. Patients that were in clinical remission were more likely to arrive late, rather than early, for scheduled therapy, compared with patients with active disease (OR 2.92 CI 1.75–4.85, p < 0.0001). Conclusion: Real life delays of <4 days from infusion protocol can probably be allowed. Delays beyond that would significantly decrease TL and might negatively affect therapy outcome. As patients arriving late for an infusion had higher rates of clinical remission than those arriving early, we assume clinical factors mainly drive patients to receive an earlier-then-scheduled infusion.